PENINGKATAN MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI ACTIVE LEARNING TIPE TRUE OR FALSE PADA SISWA KELAS V SD - Dewi Sintya, Desti; Imaningtyas; Chandra Muji Utami, Nidya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Pancasila Education aims to instill Pancasila values ​​starting from understanding basic concepts to internalizing Pancasila values ​​in everyday life. Achieving this goal is highly dependent on students' learning motivation. However, many students have low learning motivation due to teaching methods that are still conventional and less interactive. Therefore, this study aims to improve students' learning motivation through the application of the True or False Active Learning approach to the Pancasila Education subject in class V of SDN Srengseng Sawah 12 Pagi. The method used is Classroom Action Research (CAR). The subjects of this study were 27 students in class V. Data were collected through observation, questionnaires, and documentation which were then analyzed descriptively qualitatively and quantitatively. The results of the study showed that the acquisition of students' learning motivation based on seven indicators in cycle I reached a success indicator with a percentage of 85% (Good), while in cycle II the success indicator increased by 7% to 92% (Very Good). It can be concluded that the implementation of the True or False type Active Learning approach can increase students' learning motivation in the Pancasila Education subject in grade V at SDN Srengseng Sawah 12 Pagi.